THE EFFECT OF PRODUCT INNOVATION AND PRODUCT DISCOUNTS ON CONSUMER PURCHASE INTENTION ON THE TIKTOK SHOP PLATFORM - Selvyna Gusti; Husnil Khatimah (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of product innovation and product discounts on consumer purchase intention on the TikTok Shop platform. The research method used is a quantitative approach with data collection techniques through questionnaires. The research sample is active TikTok Shop users. The data analysis technique used Structural Equation Modeling Partial Least Square (SEM-PLS). The results show that product innovation has a positive and significant effect on consumer purchase intention with a coefficient value of 0.312. Meanwhile, product discounts have a positive and significant effect with a coefficient value of 0.514, and are the most dominant variables. The R-square value of 0.522 indicates that both variables are able to explain 52.2% of the variation in consumer purchase intention. This finding confirms that the combination of product innovation and discount strategies is an important factor in increasing consumer purchase intention on the TikTok Shop platform.